2022
DOI: 10.1002/btpr.3300
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption on core‐shell resins for flow‐through purifications: Effect of protein molecular size, shape, and salt concentration

Abstract: This work addresses the functional properties of the core‐shell resins Capto Core 400 and 700 for a broad range of proteins spanning 66.5 to 660 kDa in molecular mass, including bovine serum albumin (BSA) in monomer and dimer form, fibronectin, thyroglobulin, and BSA conjugates with 10 and 30 kDa poly(ethylene glycol) chains. Negatively charged latex nanoparticles (NPs) with nominal diameters of 20, 40, and 100 nm are also studied as surrogates for bioparticles. Protein binding and its trends with respect to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…This is supported by the observation that a higher protein depletion was achieved by an increasing shell cut-off for all tested columns (Figure 1B). The larger pores in the shell facilitate a higher diffusion rate of the contaminating protein components into the particle, which was also previously observed for proteins and latex nanoparticles, when comparing CC700 and CC400 [28]. In this study, residence times of at least 2 min were suggested for loading a feed containing 1 mg protein mL −1 , whereas in the present experiments, residence times of 1 min were applied, using feed containing more than 2 mg mL −1 contaminating proteins in order to reduce the process time.…”
Section: Ram Column Performance On First Usesupporting
confidence: 69%
See 3 more Smart Citations
“…This is supported by the observation that a higher protein depletion was achieved by an increasing shell cut-off for all tested columns (Figure 1B). The larger pores in the shell facilitate a higher diffusion rate of the contaminating protein components into the particle, which was also previously observed for proteins and latex nanoparticles, when comparing CC700 and CC400 [28]. In this study, residence times of at least 2 min were suggested for loading a feed containing 1 mg protein mL −1 , whereas in the present experiments, residence times of 1 min were applied, using feed containing more than 2 mg mL −1 contaminating proteins in order to reduce the process time.…”
Section: Ram Column Performance On First Usesupporting
confidence: 69%
“…Following the evaluation of the general column suitability for the model virus purification, the selected RAM columns were cleaned (NaOH and H 2 O) and re‐equilibrated up to two times for an additional usage. Only the largest available cut‐offs were evaluated for each column, as they performed best in the previous study, and it can be assumed that these show the greatest regeneration potential due to a higher diffusion rate [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, its regeneration requires the use of solvents (Konstantinidis, Reinhart, et al, 2022), it represents a unique technology and, given its suitability to LVV purification, procuring it for commercial scale manufacturing may face supply chain limitations. Finally, its adsorption mechanism is characterized by irreversible binding of solutes diffusing into the pores of the resin (Carta et al, 2022;Mi et al, 2021Mi et al, , 2023. Hence, undesired solutes of large size may be co-purified with large target solutes, such as LVVs.…”
Section: Introductionmentioning
confidence: 99%